1992
DOI: 10.1021/bp00016a012
|View full text |Cite
|
Sign up to set email alerts
|

Production and Purification of a Recombinant Elastomeric Polypeptide, G‐(VPGVG)19‐VPGV, from Escherichia coli

Abstract: An elastomeric polypeptide was produced, with the sequence G-(VPGVG)19-VPGV, as a fusion to glutathione S-transferase using the vector pGEX-3X. The fusion protein was expressed to high levels in Escherichia coli as indicated by SDS-PAGE analysis of induced cells. The fusion protein was affinity purified and cleaved with protease factor Xa, and the elastomeric polypeptide was recovered to a high degree of purity as indicated by SDS-PAGE followed by staining with CuCl2. The physical characterizations of carbon-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(112 citation statements)
references
References 17 publications
7
105
0
Order By: Relevance
“…This retard effect on electrophoretic mobility for ELRs when compared to a commercial MW marker in SDS-PAGE is well known and was previously described [1][2][3] This material is available free of charge via the Internet at http://pubs.acs.org.…”
mentioning
confidence: 67%
“…This retard effect on electrophoretic mobility for ELRs when compared to a commercial MW marker in SDS-PAGE is well known and was previously described [1][2][3] This material is available free of charge via the Internet at http://pubs.acs.org.…”
mentioning
confidence: 67%
“…Stable macroscopic matrix structures can be fabricated by the spontaneous self assembly of aqueous sapeptide solutions introduced to physiological salt-containing solutions. The self assembly of other sapeptide and protein materials has been described (9)(10)(11)(33)(34)(35)(36)(37)(38)(39). One peptide gel was reported by Aggeli et al, who found a fragment of a membrane protein that forms very stable ␤-sheet and can be processed into tape and other novel materials structures (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Several polymer-based peptide and protein self-assembly systems have also been developed by other investigators. These protein-based polymers were also designed de novo and produced through recombinant DNA biotechnology (35)(36)(37)(38)(39). Discovery and understanding of the nature of peptideand protein-based biological materials is an emerging field.…”
Section: Discussionmentioning
confidence: 99%
“…X a (McPherson et al, 1992) or exopeptidases such as dipeptidyl aminopeptidase-1 (DAP-1; Pedersen et al, 1999) or carboxypeptidase B . Whilst these enzymatic methods will generally act on the introduced accessible cleavage sequences, they have often been found to be less efficient since their kinetic rates of cleavage are affected by the accessibility of the cleavage site and the nature of the adjacent amino acid residues.…”
Section: When Does the Fusion Tag Need To Be Removed After Purification?mentioning
confidence: 99%